The Effectiveness of Mindfulness Counseling to Improve Orphan AdolescentsÔÇÖ Subjective Wellbeing - Silvianetri Silvianetri; Irman Irman; Wahidah Fitriani; M Habibullah Silvir; Che Zarrina SaÔÇÖari; Rebecca Fanany (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The main problem in this study is the lack of subjective well-being levels of orphan adolescents. The purpose of this study was to reveal empirical data related to the effectiveness of mindfulness counseling to improve the subjective well-being of orphan adolescents. The population of this research is teenagers who live in Panti Sosial Bina Remaja Padang Panjang, West Sumatra. To measure the level of subjective wellbeing using an instrument namely subjective wellbeing scale that has 32 items. The research sample are 20 teenagers who were taken randomly with simple random sampling technique. The research sample was divided into 2 groups, namely the experimental group which consisted of 10 orphaned adolescents and the control group which also consisted of 10 orphan adolescents. Treatment was given with different techniques in the experimental group and the control group. The experimental group was given mindfulness counseling, and the control group was given lectures. Each group received 6 sessions of treatment. Data analysis used independent t test, which was processed using SPSS for Windows version 20.0. Prior to hypothesis testing, prerequisite tests were conducted, namely through normality and homogeneity tests. The results showed that mindfulness counseling was effective in improving subjective well-being, with an increase in the experimental group of 43.4 points compared to the control group, and a value of P = 0.0001